2013
DOI: 10.7314/apjcp.2013.14.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MUC1 siRNA on Drug Resistance of Gastric Cancer Cells to Trastuzumab

Abstract: Trastuzumab is the first molecular targeting drug to increase the overall survival rate in advanced gastric cancer. However, it has also been found that a high intrinsic or primary trastuzumab resistance exists in some proportion of gastric cancer patients. In order to explore the mechanism of resistance to trastuzumab, firstly we investigated the expression of MUC1 (membrane-type mucin 1) in gastric cancer cells and its relationship with drug-resistance. Then using gene-silencing, we transfected a siRNA of MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
(20 reference statements)
1
16
0
Order By: Relevance
“…There is evidence that resistance to trastuzumab in HER2 positive gastric cancer is mediated through the MUC1 gene, and that silencing the MUC1 gene can reverse resistance to trastuzumab [26]. …”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…There is evidence that resistance to trastuzumab in HER2 positive gastric cancer is mediated through the MUC1 gene, and that silencing the MUC1 gene can reverse resistance to trastuzumab [26]. …”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…MUC1 has been proposed to be involved in trastuzumab resistance. MUC1 expression levels reportedly affect the antitumor effect of trastuzumab [13,14] and anti-MUC1 antibodies help overcome trastuzumab resistance [15,16]. However, these studies have examined the effect of MUC1 on trastuzumab itself but not on trastuzumabmediated ADCC.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that two single nucleotide polymorphisms (rs4072037 and rs2070803) in the MUC1 gene has been identified in gastric cancer patients and may have a prospective role in the stratification of high-risk subjects [171]. The overexpression of MUC1 and MUC4 also mediates resistance to the trastuzumab, a monoclonal antibody against HER-2/neu [172,173] siRNA to MUC1 was tested in trastuzumab drug resistance cells and a better response to the drug was seen in siRNA treated drug resistant cell when compared to control or junk siRNA treatment [174].…”
Section: Stomach Gastric Carcinomamentioning
confidence: 99%